A redescription of ’Megalosaurus’ hesperis (Dinosauria, Theropoda) from the Inferior Oolite (Bajocian, Middle Jurassic) of Dorset, United Kingdom - Benson, Roger B. J. (Zootaxa, 2008)
‘Megalosaurus’ hesperis from the Inferior Oolite (Bajocian, Middle Jurassic) of Dorset, UK is redescribed. Several features of ‘M.’ hesperis demonstrate that it is distinct from the lectotype dentary of Megalosaurus: an enlarged, subcircular third alveolus and subcylindrical, anteriorly inclined anterior dentary teeth; an anterior Meckelian foramen located almost directly anterior to the posterior Meckelian foramen; low interdental plates; and a prominent lip bounding the Meckelian groove ventrally, anterior to the Meckelian fossa. Therefore a new genus, Duriavenator, is erected to form the new combination D. hesperis. D. hesperis possesses two autapomorphies of the maxilla: a deep groove on dorsal surface of the jugal process containing numerous pneumatic foramina; and an array of small foramina in the ventral part of the articular surface for the premaxilla. Several features confirm the tetanuran affinities of D. hesperis: a prominent anterior process of the maxilla; the presence of band-like dental enamel wrinkles; the maxillary ’fenestra’ is present but takes the form of an imperforate fossa (a spinosauroid synapomorphy); and the paradental groove is wide anteriorly, defining a distinct gap between the interdental plates and the medial wall of the dentary (a synapomorphy of Spinosauridae + Megalosauridae). Older records of tetanurans have been proposed, but most of these have been refuted and detailed re-examination of other early reports is warranted to establish the date of origin of this clade. An early Middle Jurassic origin of tetanurans is preferred.